Edgar, King of the English, 959-975 : new interpretations - Scragg, D. G. (Publications of the Manchester Centre for Anglo-Saxon Studies, 2008)
Fresh assessments of Edgar's reign, reappraising key elements using documentary, coin, and pictorial evidence.